DETERMINAN KINERJA PERUSAHAAN PADA INDUSTRI PENGHASIL BAHAN BAKU YANG TERDAFTAR DI BEI PERIODE 2012-2016 - Syarief, Arief Hamdan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
The research objective was to analyze the effect of company size, capital structure, agency cost and managerial ownership on company performance with an economic value added approach in raw material producing industries listed on the Indonesia Stock Exchange for the period 2012 - 2016. The research data in this study were obtained from secondary data, namely data already available in financial reports or annual reports published by companies in the industrial sector producing raw materials with a total of 17 companies. The analytical tool used is multiple linear regression and hypothesis testing using t test calculations. The results of the study show that firm size and capital structure have a positive effect on economic value added, while agency costs and managerial ownership have no effect on economic value added.